The Modern Use of an Ancient Plant: Exploring the Antioxidant and Nutraceutical Potential of the Maltese Mushroom (Cynomorium Coccineum L.) - Paolo Zucca; Sidonie Bellot; Antonio Rescigno (MDPI AG, 2019)
In the continuous scientific search for new safe and effective drugs, there has recently been a rediscovery of natural substances as a potential reservoir of innovative therapeutic solutions for human health, with the prospect of integrating with and sometimes replacing conventional drugs. Cynomorium coccineum subsp. coccineum is a holoparasitic plant well known in ethnopharmacology, although its current use as a curative remedy is reported only in some ethnic groups of North Africa and the Arabian Peninsula. Often known as ‘Maltese mushroom’ due to its unique appearance and the absence of chlorophyll, C. coccineum is present in almost all of the Mediterranean Basin. It is only recently that a few research groups have begun to look for confirmation of some of its traditional uses to highlight previously unknown biological activities. Here, we review the recent scientific findings on the plant’s phytochemistry and the most significant descriptions of some of its antioxidant and biological activities (antimicrobial, anticancer, pro-erectile, and anti-tyrosinase enzyme) both in vivo and in vitro. Some of these may be promising from the perspective of food and cosmetic formulations. The purpose of this review is to provide an initial impetus to those who, in the foreseeable future, will want to increase the knowledge and possible applications of this plant full of history, charm, and mystery.